From sword to shield the transformation of the corporate income tax, 1861 to present - Bank, Steven A., 1969- (New York ; Oxford : Oxford University Press, 2010)
This historical account of the evolution of the corporate income tax in America explains the origins of corporate income tax. Banks shows that political, economic, and social forces transformed it from a sword against evasion of the individual income tax to a shield against government and shareholder interference.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Corporations -- Taxation -- United States -- History; Corporations -- Taxation -- Law and legislation -- United States -- History